CCT8 recovers WTp53-suppressed cell cycle evolution and EMT to promote colorectal cancer progression - Qing Liao (Nature Publishing Group, 2021)
Abstract LIM and SH3 protein 1 (LASP1) is a metastasis-related protein reported to enhance tumor progression in colorectal cancer (CRC). However, the underlying mechanism is still elusive. The chaperonin protein containing TCP1 (CCT) is a cellular molecular chaperone complex, which is necessary for the correct folding of many proteins. It contains eight subunits, CCT1-8. CCT8 is overexpressed in many cancers, however, studies on CCT8 are limited and its role on CRC development and progression remains elusive. In this study, we confirmed that CCT8 and LASP1 can interact with each other and express positively in CRC cells. CCT8 could recover the ability of LASP1 to promote the invasion of CRC; CCT8 could significantly promote the proliferation, invasion, and metastasis of colorectal cells in vivo and in vitro. Mechanically, CCT8 inhibited the entry of WTp53 into the nucleus, and there was a negative correlation between the expression of CCT8 and the nuclear expression of WTp53 in clinical colorectal tissues. CCT8 promoted the cell cycle evolution and EMT progression of CRC by inhibiting the entry of WTp53 into the nucleus. Clinically, CCT8 was highly expressed in CRC. More importantly, the overall survival of CRC patients with high expression of CCT8 was worse than that of patients with low expression of CCT8. These findings indicate that as LASP1-modulated proteins, CCT8 plays a key role in promoting the progression of colorectal cancer, which provides a potential target for clinical intervention in patients with colorectal cancer.